Implementasi Model TPACK Melalui Media ZepQuiz Untuk Meningkatkan Pemahaman Siswa Tentang Aliran-Aliran Ilmu Kalam Dalam Mata Pelajaran Aqidah Akhlak di Kelas XI. 1 MA MAI Purwakarta - Nugraha, Ilah Nursolihah; Munir, Dede Rizal; Setiawan, Usep (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to improve students understanding of the subject of Islamic Theology through the application of the Technological Pedagogical and Content Knowledge (TPACK) model using ZepQuiz media in Aqidah Akhlak learning. The research method used was Classroom Action Research (CAR) based on the Kemmis McTaggart model, which was conducted in two cycles. The research subjects were 18 students of class XI.1 MA MAI Purwakarta. The research instruments were a Likert scale questionnaire and an observation sheet. The results showed a significant increase in the four main indicators. In the Content Knowledge (CK) indicator, the average score increased from 1.29 to 3.27 (excellent category). Pedagogical Knowledge (PK) increased from 2.30 to 3.40 (excellent category), Technological Knowledge (TK) increased from 3.17 to 3.70 (excellent category), and TPACK increased from 2.84 to 3.46 (excellent category). These results indicate that the application of the TPACK model through the ZepQuiz media can improve students' conceptual understanding and active engagement in Aqidah Akhlak learning. The conclusion of this study confirms that the integration of content, pedagogy, and technology in religious education can be an effective strategy for improving the quality of learning, especially for abstract material such as Kalam.